2010
DOI: 10.1111/j.1468-1293.2010.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the long-term durability of nevirapine, efavirenz and lopinavir in routine clinical practice in Europe: a EuroSIDA study

Abstract: ObjectivesThe durability of combination antiretroviral therapy (cART) regimens can be measured as time to discontinuation because of toxicity or treatment failure, development of clinical disease or serious long-term adverse events. The aim of this analysis was to compare the durability of nevirapine, efavirenz and lopinavir regimens based on these measures. MethodsPatients starting a nevirapine, efavirenz or lopinavir-based cART regimen for the first time after 1 January 2000 were included in the analysis. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
1
17
1
Order By: Relevance
“…On the other hand, a prospective, observational trial involving more than 20 000 patients showed a lower incidence of death and AIDS-defining illness, as well as lower risk of virologic failure at 12 months for efavirenz compared with nevirapine [39]. Results obtained in routine clinical practice in Europe also showed that patients starting efavirenz had a 48% lower risk of discontinuation due to treatment failure compared with the nevirapine group (however, in this trial about 60% of patients were treatment-experienced) [40]. …”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, a prospective, observational trial involving more than 20 000 patients showed a lower incidence of death and AIDS-defining illness, as well as lower risk of virologic failure at 12 months for efavirenz compared with nevirapine [39]. Results obtained in routine clinical practice in Europe also showed that patients starting efavirenz had a 48% lower risk of discontinuation due to treatment failure compared with the nevirapine group (however, in this trial about 60% of patients were treatment-experienced) [40]. …”
Section: Discussionmentioning
confidence: 94%
“…The concentrations required for the effect are well in the range of plasma concentrations determined in patients under lopinavir treatment [61]. The observed eryptosis and hemolysis may thus well explain the anemia following lopinavir treatment [14].…”
Section: Discussionmentioning
confidence: 55%
“…Side effects of lopinavir treatment include anemia [14]. Lopinavir may induce proteotoxic stress [15,16], trigger oxidative stress [16], and suppress NF-κB activity [17].…”
Section: Introductionmentioning
confidence: 99%
“…An non nucleoside reverse transcriptase inhibitor (NNRTI) based regimen is preferred over protease inhibitors (PI/r) based regimens considering similar potency, convenience, lesser expense and lower prevalence of primary resistance in the population5355. Efavirenz (EFV) is preferred over nevirapine (NVP) when concomitant use of rifampicin is indicated, patients preference for once daily (lower pill burden) regimen and if pre-therapy CD4 count is >250/mm 3 and >400/mm 3 in women and men respectively56–60.…”
Section: What To Start With? (Table Ii)mentioning
confidence: 99%